Around the world in 60 seconds : the Nas daily journey : 1,000 days, 64 countries, 1 beautiful planet - Yassin, Nuseir, 1992-; Kluger, Bruce (U.S.A: HarperOne, 2019)
"A beautifully photographed, perspective-shifting global adventure that shines a fascinating light on places and people well off the beaten path, from Nas Daily, the 1-minute video platform with massive international following"--
India : how India blew my mind -- Armenia : the country I couldn't find on a map -- Canada : I had a dream -- The Philippines : my biggest surprise -- Puerto Rico : how strong is an American passport? -- Malaysia : the airport prisoner -- Japan : imperfectly perfect -- Malta : oh, my Malta! -- Israel : strangers make the best friends -- Pakistan : how I entered a country I'm banned from -- Jerusalem : Jews vs. Arabs -- Japan : my Japanese friends -- Israel : coming home -- The Maldives : let your hair down -- The Philippines : I visited a war zone -- The world : one guy is all it takes -- Africa : why are we blind to Africa? -- Mexico : the Mexico you never see -- Rwanda : forgiveness, justice, and the future -- Singapore : always a step ahead -- Zimbabwe: free at last -- China : from fake news to feng shui -- Iceland : there is a ninth planet -- Australia : the wonder down under -- Papua New Guinea : mi laikim kantri! -- Epilogue: Journey's end.
Keywords: Yassin, Nuseir, -- 1992- -- Travel; Nas daily (Video blog); Voyages around the world